Caffeine Determination at a Carbon Fiber Ultramicroelectrodes by Fast-Scan Cyclic Voltammetry - Nunes, Ronaldo S. [UNESP] (2012)
Caffeine determination using a fast-scan voltammetric procedure at a carbon fiber ultramicroelectrode (CF-UME) is described. The CF-UME was submitted to electrochemical pretreatment. Parameters such as number of acquisition cycles, scan rate, potential window, and the electrochemical surface pretreatment were optimized. Using the optimized conditions, it was possible to achieve a LDR from 10.0 up to 200 mu mol L-1, with a LOD of 3.33 mu mol L-1. The method has been applied in the determination of caffeine in commercial samples, with errors of 1.0-3.5% in relation to the label values and recoveries of 97-114% within the linear range.